Deformations of Anisotropic Layered Materials - Clements, D.L.; Hill, D.L.; Mazumdar, J. (Engineering Transactions, 1982)
The problem of determining the stress and displacement fields in an inhomogeneous material consisting of three bounded anisotropic layers is considered. Numerical values for the stress on the interface are obtained and the effect of a crack on the stress field is examined.